Capsules from synthetic diblock-peptides as potential artificial oxygen carriers. (4th July 2021) - Feng, Huayang; Linders, Jürgen; Myszkowska, Sascha; Mayer, Christian
Abstract: The design of an encapsulation system consisting of a synthetic peptide which is fully biodegradable into non-toxic constituents. This system should be capable of encapsulating perfluorinated hydrocarbons and should be a promising basis for oxygen carriers to be used as artificial blood replacement. A diblock-peptide is synthesised following a phosgene-free method and characterised by 1 H-NMR. Subsequently, this diblock-peptide is self-assembled with perfluorodecalin (PFD) to form PFD-filled capsules as potential artificial oxygen carriers allowing for rapid oxygen uptake and release. The diblock-peptide Bu-PAsp10 -PPhe10 is successfully synthesised and used to encapsulate PFD. The capsules have a spherical shape with an average diameter of 360 nm in stable aqueous dispersion. NMR measurements prove their physical capability for reversible uptake and release of oxygen. The resulting capsules are expected to be fully biodegradable and possibly could act as oxygen carriers for artificial blood replacement.